Experimental Infection of Foot and Mouth Disease in Indian Sheep and Goats - Muthukrishnan, Madhanmohan; Singanallur Balasubramanian, Nagendrakumar; Villuppanoor Alwar, Srinivasan (Frontiers in Veterinary Science, 2020)
Foot-and-mouth disease (FMD) is an economically important contagious disease of livestock mainly cattle, buffalo, sheep, goats and pig. There is limited data available on pathogenesis of foot and mouth disease in goats. In the study, the sheep and goats were infected experimentally with a serotype O foot-and-mouth disease virus by different challenge routes. The sheep and goats challenged by coronary band route and coronary band and intra-dermo-lingual route exhibited FMD clinical signs at 2 to 5 days post challenge. Whereas intra-dermo-lingual challenged sheep and goats did not exhibit FMD clinical signs. Live virus could be isolated from blood of infected sheep and goats at 2 to 5 days post challenge. Viral RNA could be detected from blood of infected sheep and goats at 1to10 days post challenge. The neutralizing antibody titre was detected at 10 days post challenge and maintained up to 35 days post challenge in all infected sheep and goats. Non structural protein (NSP) antibodies were detected as early as 5 to10 days post challenge and remain positive up to 35 days post challenge in the infected sheep and goats. In conclusion, the pathogenesis of sheep and goats with serotype O foot and mouth disease virus by different challenge routes could be demonstrated.